Molecular epidemiology of bloodstreamassociatedEscherichia coliST131 H30‐Rx subclone infection in a region with high quinolone resistance. Issue 4 (April 2016) - Can, Fusun; Kurt‐Azap, Ozlem; Nurtop, Elif; Ispir, Pelin; Seref, Ceren; Ergonul, Onder
Abstract : N/A: Bloodstream infections caused by Escherichia coli ST131 and ST131 H30‐Rx subclones have emerged worldwide. This study was carried out to evaluate the prevalence of the ST131‐Rx subclone and characterize the virulence properties of the Rx isolates among the bloodstream E . coli isolates. A total of 297 non‐duplicated E. coli bloodstream isolates were studied. Antibiotic susceptibilities were tested using the disc diffusion method. PCR amplification and sequencing was used to identify ST131 and H30‐Rx, the virulence gene, the b‐lactamase and virotype. Quinolone resistance among bacteraemic E. coli strains was 51 %, and it was 98% among E. coli ST131 isolates. The ST131 isolates accounted for 16% (49) of all isolates and all ST131 isolates belonged to the extraintestinal pathogenic E. coli. The proportion of H30 subclone among the ST131 isolates was 98 %, and 75% of H30 isolates belonged to the H30‐Rx subclone. The prevalence of ST131 increased from 13 to 23% in 4 years; however, there was a decrease in the ratio of H30‐Rx infections. CTX‐M‐15 was detected in 85% of ST131 and all of the H30‐Rx isolates. The virulence genes associated with adhesion, cell protection, iron uptake and toxins ( papA, iha, kpsMTII, iut and sat ) were more common in ST131 than in non‐ST131 isolates. Most of the ST131 and H30‐Rx isolates were of the C virotype. All papA ‐positive isolates were in virotype C. The E. coli ST131 clone has increased rapidly among bloodstream isolates. However, a decrease in the proportion of the H30‐Rx subclone in the quinolone‐resistant population suggests the possibility of dissemination of other virulent and quinolone‐resistant subclones in hospital settings.